De la DCTI au CENADI : Logiques endogènes et contraintes exogènes de la politique publique de l’informatisation du Cameroun depuis 1966 - Thomas ATENGA (Tic & Société)
How is the cameroonian public policy of « computerization» build since 1966? What are the local rationalities that govern this process? How does this process integrate injunctions coming from bilateral and multilateral partners ? How cameroonian government combines these injunctions with his development needs? These are the main questions that structure this paper. It is based on the example of the National Development Centre for Computerization (CENADI) supposed to drive this policy. This research analyses the singular trajectory of this public policy: its successes, its difficulties, its challenges. At this end, a particular attention is drawn on the state’s role, the coming up of new stakeholders, the perverse effects of the privatization of this policy. Our analyses are based on interviews with staff of CENADI as well as stakeholders of the private sector. It advances the idea that within this long while, the computerization policy of Cameroon experienced two major cycles, with internal sequences taking particular configurations. The first cycle starts during monolithic political system, when the state was the only convenor of any economic, social and cultural policy. The state invests a lot of means, not always followed by results. The second cycle begins with the first structural adjustment program in September 1988. The State is pushed aside by new stakeholders, donors and international organizations.